2014
DOI: 10.1177/1071100714557861
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coronal Plane Subtalar Joint Alignment in Peritalar Subluxation via Weight-Bearing Multiplanar Imaging

Abstract: Inftal-hor and inftal-suptal angles provided a reliable means of evaluating the orientation of the subtalar joint axis in AAFD via MP-WB, and showed that the subtalar joint had increased valgus orientation in AAFD compared to controls. This may allow for identification of patients at risk for developing AAFD, and could potentially be used in guiding operative reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
79
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 15 publications
2
79
0
2
Order By: Relevance
“…Studies using single weight‐bearing CT images showed significant differences in the orientation of the posterior facet from anterior to posterior (screw shape morphology) . We found similar results using DRRs: The posterior aspect of the joint (45/10 degrees Broden view) showed a more varus inclination compared to the anterior aspect, which was in a more neutral alignment.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Studies using single weight‐bearing CT images showed significant differences in the orientation of the posterior facet from anterior to posterior (screw shape morphology) . We found similar results using DRRs: The posterior aspect of the joint (45/10 degrees Broden view) showed a more varus inclination compared to the anterior aspect, which was in a more neutral alignment.…”
Section: Discussionsupporting
confidence: 73%
“…The role the subtalar joint plays in the development of ankle joint disorders has been investigated extensively in recent years . It has been suggested that the subtalar joint morphology (e.g., convex vs. flat) and orientation (e.g., slope) specifically of the posterior facet may influence the evolution of ankle osteoarthritis .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The posterior facet of the subtalar joint is the largest and is always present. There is variation in its orientation and this has been linked to the development and progression of osteoarthritis, and to adult‐acquired flatfoot deformity . The posterior facet is convex in a sagittally oriented plane and flat or slightly concave in a coronally oriented plane …”
mentioning
confidence: 99%